Convergence of biofilm successional trajectories initiated during contrasting seasons - Wang, Jing; Peipoch, Marc; Guo, Xiaoxiao; Kan, Jinjun (Frontiers in Microbiology, 2022)
Biofilm communities play a major role in explaining the temporal variation of biogeochemical conditions in freshwater ecosystems, and yet we know little about how these complex microbial communities change over time (aka succession), and from different initial conditions, in comparison to other stream communities. This has resulted in limited knowledge on how biofilm community structure and microbial colonization vary over relevant time scales to become mature biofilms capable of significant alteration of the freshwater environment in which they live. Here, we monitored successional trajectories of biofilm communities from summer and winter in a headwater stream and evaluated their structural state over time by DNA high-throughput sequencing. Significant differences in biofilm composition were observed when microbial colonization started in the summer vs. winter seasons, with higher percentage of algae (Bacillariophyta) and Bacteroidetes in winter-initiated samples but higher abundance of Proteobacteria (e.g., Rhizobiales, Rhodobacterales, Sphingomonadales, and Burkholderiales), Actinobacteria, and Chloroflexi in summer-initiated samples. Interestingly, results showed that despite seasonal effects on early biofilm succession, biofilm community structures converged after 70 days, suggesting the existence of a stable, mature community in the stream that is independent of the environmental conditions during biofilm colonization. Overall, our results show that algae are important in the early development of biofilm communities during winter, while heterotrophic bacteria play a more critical role during summer colonization and development of biofilms.